Teologia em mosaico: o novo cenário teológico latino-americano nos anos 90. Rumo a um paradigma ecumênico crítico - Bock, Carlos Gilberto (2002)
Significant changes at global level in the 90s have had their effect upon Liberation Theology in Latin America. Chapter one of this thesis presents the analyses of three representative Brazilian theologians (C. Boff, L. Boff, H. Assmann). From their own personal and theological perspectives, they indicate what are the most appropriated theological outlines for Latin American theology at this historical moment. In this chapter I also deal with the hypothesis of a paradigm shift in Liberation Theology as an answer to the crisis experienced. It is observed that this period is characterized by a plurality of paradigms in coexistence. In chapter two I try to show that, in the midst of the new scenarios of the 90s, Latin-American theology reveals important developments and dislocations both of methodological and epistemological nature. These are described and analyzed in this chapter. In the third and conclusive chapter, I sustain the thesis that the changes previously identified cannot be, in their totality, subsumed within the original paradigm of Liberation Theology. It is observed that this new phase is characterized by a new theological pluralism which requires an ecumenical critical (macro)paradigm. On the one hand, in what concerns pluralism, we reject the perspective of theological fragmentation. On the other hand, in what concerns the demands for unity, any solution is denied which seeks to skip or to harmonize the differences. The contention is that an ecumenical critical paradigm is the most appropriate for ongoing theological reflection. This paradigm promotes the plural coexistence and a mutual fertilization between the distinctive perspectives.